Hebräisch Biblisch-Hebräische Unterrichtsgrammatik - Krause, Martin 1942-2020; Pietsch, Michael 1967-; Rösel, Martin 1961- (Berlin Boston De Gruyter, 2020)
Two Volume Edition
Teil 1: Grammatik
Teil 2: Texte, Vokabulare, Tabellen
This book is designed as an accompanying textbook for Hebrew instruction. It provides the student the greatest number of options for selecting and applying different teaching methods. The student's tasks of learning, looking up words, and reviewing are expedited through clear organization of the learning material. The work has a consistent two-color design, making unusual features easier to remember. Features a consistent two-colored design, with targeted references to unusual features, root modifications, and problems in translation. Colored letter tabs ease navigation through the book
In German
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Hebrew language -- Grammar -- Textbooks; RELIGION / General; RELIGION / Biblical Reference / Language Study; RELIGION / Biblical Reference / Dictionaries & Encyclopedias; Bibel; Biblisches Hebräisch; Hebräischunterricht; Altes Testament; FOREIGN LANGUAGE STUDY / Hebrew; RELIGION / Biblical Criticism & Interpretation / Old Testament; Biblical Hebrew; Grammar; Lehrbuch; Lehr- und Lernressource